Significance of Membranous Urethral Length for Recovery From Postoperative Urinary Incontinence Following Holmium Laser Enucleation of the Prostate - Shintaro Oka; Keita Kobayashi; Kenji Matsuda; Kimio Takai (International Neurourology Journal, 2020)
Purpose The aim of this study was to determine the significance of the membranous urethral length (MUL), including the thickness of the urethral sphincter, for recovery from postoperative stress urinary incontinence (SUI) following holmium laser enucleation of the prostate (HoLEP). Methods We analyzed 78 patients who underwent HoLEP between June 2013 and September 2018, all of whom preoperatively received magnetic resonance imaging. MUL was measured using sagittal T2-weighted fast spin-echo images. The clinical and anatomical factors associated with MUL were evaluated. The recovery time of urinary incontinence was compared between patients with a long MUL (≥14 mm) and a short MUL (<14 mm). SUI included both stress and mixed urinary incontinence. Continence was defined as complete dryness. Results The median MUL in patients without incontinence at 1 month postoperatively was significantly longer than the MUL in patients with incontinence (15.3 mm vs. 12.7 mm, P<0.001). The continence rates at 1 month after HoLEP in patients with longer MULs and shorter MULs were 80.4% and 30.0%, respectively. The recovery time of urinary incontinence in patients with longer MULs (≥14 mm) was significantly shorter than that in patients with shorter MULs (<14 mm) (log-rank test, P=0.001). After 6 months, the continence rates in patients with longer MULs and shorter MULs were similar (97%). MUL was significantly correlated with the recovery period of urinary incontinence (r=-0.459, P<0.001). Conclusions MUL was useful for predicting early recovery from urinary incontinence following HoLEP. This study provides evidence that postoperative urinary incontinence following a transurethral procedure for benign prostatic hyperplasia was associated with anatomical factors. A long MUL was associated with better tolerance to urinary sphincter damage by the transurethral procedure.